A Comprehensive Approach for the Design of Solvent-based Adhesive Products using Generalized Disjunctive Programming - Cui,J; Jonuzaj,S; Adjiman,C (Elsevier B.V., 2018)
In this work, we present a comprehensive and systematic methodology for the design of optimal adhesive products within the computer-aided product design (CAPD) framework. In the proposed approach, the optimal number, identities and compositions of active ingredients and solvents in the final product are determined simultaneously. Generalised Disjunctive Programming (GDP) is employed to formulate the main design decisions of the problem (i.e., how many ingredients should be included, which active ingredients and solvents compounds should be used and in what proportions). The design methodology has been applied to identifying cheap and environmentally friendly acrylic adhesives, which are commonly used in construction.